Early seed plants from Western Gondwana: Paleobiogeographical and ecological implications based on Tournaisian (Lower Carboniferous) records from Argentina - Prestianni, C. (2014)
The oldest seed occurrences in Western Gondwana have been recognized in a new stratigraphic section located in Western Argentina (Precordillera Basin). Palynological evidence indicates an Early Mississippian (probably Tournaisian) age for this new succession. The two identified early seeds generas, Pseudosporogonites cf. hallei and Warsteinia sancheziae n. sp. were up to now considered as restricted to the Devonian of Laurussia. This finding suggests a dispersal of earliest spermatophytes between Laurussia and Gondwana during Devonian/Tournaisian times, thus accounting for the Rheic Ocean as a surmountable biogeographic barrier for continental biotas. Alternatively, contrasting biogeographic hypotheses dealing with early spermatophytes rising in paleotropics and then displacing herbaceous communities of non-spermatophytes typical from cool high latitudinal regions, are explored for explaining the recognized paleobiogeographical pattern. The new information supports a weak impact of the Devonian/Carboniferous biotic crisis on earliest seed plant diversity. Based on preliminary evidences of niches differentiation and ecological dynamics probably affected by wildfires, Tournaisian Gondwanan plant communities from high latitudes are interpreted as being more complex than previously thought, and more similar to those reported from Laurussia. In addition, their discovery in a sedimentary environment associated to glacigenic deposits, show that this new record might be linked to the coeval glacial age widely recorded elsewhere in Gondwana.